PENGARUH INDEPENDENSI, BEBAN KERJA, TEKANAN WAKTU, DAN FEE AUDIT TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI SURABAYA - Savira Adryanti Firdasari; Rudi Pratono (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
The credibility of financial statements depends heavily on the quality of audits conducted by independent auditors. A decline in audit quality is believed to be influenced by various factors, including independence, workload, time pressure, and audit fees. This study aims to test and analyze the effects of independence, workload, time pressure, and audit fees on audit quality at Public Accounting Firms (PAFs) in the Surabaya area. This study employs a quantitative approach using inferential statistical analysis. The study population comprises all auditors at PAFs in Surabaya who are actively registered with the Financial Services Authority (OJK). A purposive sampling technique was used, resulting in 91 respondents. Primary data were collected through the distribution of structured questionnaires using a five-point Likert scale. Data analysis was conducted through data quality checks, tests of classical assumptions, and hypothesis testing using multiple linear regression analysis with IBM SPSS Statistics version 23. The results indicate that, when analyzed individually, the independent variables have a positive and significant effect on audit quality, whereas workload, time pressure, and audit fees do not have a significant effect. Simultaneously, these four variables influence audit quality; however, the coefficient of determination (R² = 0.184) indicates that the research model can explain only 18.4% of the variation in audit quality, while the remaining 81.6% is influenced by other factors outside the model. These findings indicate that auditor independence is the most influential variable in the research model regarding audit quality. On the other hand, the low value of the coefficient of determination suggests that there are still other factors outside the model that have a greater impact on audit quality, which should be examined in future research.